Pengaruh Growth Opportunity dan Capital Expenditure terhadap Nilai Perusahaan Transportasi yang Terdaftar di Bursa Efek Indonesia - Vika Sintia; Aminar Sutra Dewi (Lembaga Yasin AlSys, 2025)
The current transportation challenges in Indonesia are characterized by digitalization and technological innovation that affect firm value in this sector. Transportation companies that adopt digital technologies tend to have higher market value because they are better able to enhance profitability and competitiveness. In addition, global pressure to reduce carbon emissions encourages companies to shift toward electric vehicles, environmentally friendly fuels, and low-emission technologies. This study aims to analyze the effect of Growth Opportunity and Capital Expenditure on the firm value of transportation companies listed on the Indonesia Stock Exchange (IDX). The research population comprises all transportation sector companies listed on the IDX during the 2019–2023 period, with purposive sampling yielding 65 companies as the research sample. Data were analyzed using panel data regression with the support of the EViews application. The results indicate that Growth Opportunity has no significant effect on the firm value of transportation companies, whereas Capital Expenditure has a significantly negative effect on firm value. These findings suggest that growth opportunities are not yet fully reflected in market valuation, while suboptimally managed capital expenditure policies tend to be responded to negatively by the market, indicating that management needs to design more selective investment strategies that are aligned with the demands of digitalization and environmental sustainability.